The Effectiveness of The “PRAAT” Application in Improving Students' Phonemes Pronunciation - Dian Shafwati; Endang Komariah; Feni Munifatullah (Edukasi Lingua Sastra, 2025)
This study aims to examine the effectiveness of the PRAAT application in improving students' pronunciation, focusing on close mid vowels, plosive consonants, and fricative consonants. Pre-test and post-test data were collected from 50 participants to evaluate changes in pronunciation after the intervention using PRAAT. The average spectrum deviation in the pre-test was 24.5%, which decreased to 14.3% in the post-test, with a total gain of 10.2%. This significant reduction indicates an improvement in pronunciation, approaching the standard of native speakers in the analyzed phoneme categories. Statistical analysis revealed a significant change with a p-value < 0.001, affirming that PRAAT plays a crucial role in enhancing students' pronunciation quality. These findings provide empirical evidence that PRAAT is effective as a tool for improving the pronunciation of specific phonemes in language learning and recommend its broader application in educational contexts.